The Autonomy of Indonesian Islamic Court: Inventing and Refining ‘Broken Marriage’ as a Unilateral and No-Fault Divorce Ground - Farabi, Al (Al-Ahwal: Jurnal Hukum Keluarga Islam, 2025)
This article discusses important developments of marriage and divorce norms within the Islamic Chamber of the Supreme Court. Focusing on broken marriage ground, this article explores landmark decisions, Supreme Court regulations, Supreme Court circular letters, and yearly plenary meetings. In addition, interviews with judges and emerging discourse available in the quarterly magazine Peradilan Agama, from 2013 onwards, and relevant decisions by the Constitutional Court were also consulted. Employing a critical and chronological legal analysis, the discussion reveals a consistent trend of judicial law-making as apparent in the invention of ‘broken marriage’ as a unilateral and no-fault divorce ground to provide a better and more equal court access for both men and women. However, judges can still employ consideration of fault, especially when the ‘fault’ is relevant to a spouse’s post-divorce rights. These legal breakthroughs show the autonomy of Islamic court, especially to bridge the gaps between a formal application of law and a sense of justice in society. The judges’ autonomy is crucial as the more responsive attitude enhances their social recognition and the court’s legitimacy before the society. In fact, accommodation is not the only logic that works as the judges have also been very careful to ensure that developments do not work against the established interpretation of law and ‘core values’ in Islam. This finding demonstrates that the Islamic courts have served as strategic loci not only for the development of law but also for the encounter of different normative systems. [Artikel ini membahas perkembangan penting mengenai norma-norma perkawinan dan perceraian dalam Kamar Agama Mahkamah Agung. Dengan berfokus pada alasan perceraian karena “perkawinan yang pecah” (broken marriage), artikel ini menelusuri putusan-putusan penting, peraturan Mahkamah Agung, surat edaran Mahkamah Agung, dan hasil rapat pleno tahunan. Selain itu, wawancara dengan para hakim serta wacana yang berkembang dalam majalah triwulanan Peradilan Agama sejak 2013, dan putusan-putusan relevan dari Mahkamah Konstitusi juga dijadikan rujukan. Dengan menggunakan analisis hukum kritis dan kronologis, pembahasan ini mengungkap tren konsisten dalam pembentukan hukum oleh peradilan, yang tampak dalam perumusan “perkawinan yang pecah” sebagai alasan perceraian sepihak dan tanpa kesalahan (unilateral and no-fault divorce ground) untuk memberikan akses peradilan yang lebih baik dan setara bagi laki-laki dan perempuan. Namun demikian, hakim tetap dapat mempertimbangkan unsur kesalahan, terutama ketika “kesalahan” tersebut berkaitan dengan hak-hak pasca-cerai seorang pasangan. Terobosan-terobosan hukum ini menunjukkan adanya otonomi peradilan agama, terutama dalam menjembatani kesenjangan antara penerapan hukum secara formal dan rasa keadilan dalam masyarakat. Otonomi hakim sangat penting karena sikap yang lebih responsif meningkatkan pengakuan sosial dan legitimasi peradilan di hadapan masyarakat. Bahkan, akomodasi bukan satu-satunya logika yang bekerja, karena para hakim juga sangat berhati-hati memastikan bahwa perkembangan tersebut tidak bertentangan dengan interpretasi hukum yang sudah mapan dan “nilai-nilai inti” dalam Islam. Temuan ini menunjukkan bahwa peradilan agama telah menjadi lokus strategis bukan hanya bagi perkembangan hukum, tetapi juga bagi perjumpaan berbagai sistem normatif.]